DIGITALISASI SISTEM INFORMASI MANAJEMEN PENDIDIKAN DAN IMPLIKASINYA TERHADAP MUTU PENDIDIKAN DI ERA DIGITAL - Livia Sildayanti Mokodongan; Devinta Fatlunia Mokodompit; Muh Yhudi Agus Setiawan (Hijri, 2026)
The development of digital technology has brought significant changes in various sectors, including education. One form of transformation that has emerged is the digitalization of educational management information systems, which support administrative management, data processing, and decision-making in educational institutions. This study aims to analyze the digitalization of educational management information systems and its implications for educational quality in the digital era. This research employed a literature review method with a qualitative descriptive approach by examining 20 scientific journals, electronic books, and relevant academic documents. The findings indicate that the digitalization of educational management information systems contributes positively to improving administrative efficiency, data accuracy, academic service quality, and the effectiveness of data-based decision-making. However, its implementation still faces several challenges, including limited infrastructure, low digital literacy among human resources, and data security issues. Thus, the digitalization of educational management information systems contributes significantly to improving educational quality in the digital era and supports more adaptive and effective educational governance.